The Locality of Indonesian Language and Literature in a Global World: Quo Vadis? - Heru Marwara (Universitas Negeri Surabaya, 2025)
This article examines the future and sustainability of Indonesian language and literature in the context of globality. It raises the critical question: quo vadis — where is the locality of Indonesian language-literature headed amid global pressures? Globalization, while offering opportunities, poses significant challenges to the maintenance of local values and cultural identity embedded in the language and literary expressions of Indonesia. Using a critical literature review approach, the study explores threats to and strategies for preserving the uniqueness of Indonesian language-literature, including adaptation to digital platforms, media convergence, international collaboration, and creative innovations in literary production and dissemination. The findings suggest that the sustainability of Indonesian language-literature depends heavily on its capacity for strategic adaptation, innovation, and active promotion, ensuring that local identity is preserved while engaging with global audiences.